THE EFFECT OF ENVIRONMENTAL PERFORMANCE AND CORPORATE SOCIAL RESPONSIBILITY ON THE FINANCIAL PERFORMANCE OF MANUFACTURING COMPANIES IN THE PLASTIC AND PACKAGING INDUSTRY SUB SECTOR LISTED ON THE INDONESIA STOCK EXCHANGE - Dea Laila Puspita; Debbi Chyntia Ovami (CV. Radja Publika, 2025)
Abstract*